2018
DOI: 10.1002/ana.25300
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Fatal Insomnia in Europe: Phenotypic Features and Diagnostic Challenges

Abstract: sFI is a disease of young or middle-aged adults, which is difficult to reconcile with the hypothesis of a spontaneous etiology related to stochastic, age-related PrP misfolding. The combination of psychiatric and/or sleep-related symptoms with oculomotor abnormalities represents an early peculiar clinical feature of sFI to be valued in the differential diagnosis. Video-polysomnography, FDG-PET, and especially CSF prion RT-QuIC and NfL constitute the most promising supportive diagnostic tests in vivo. Ann Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…sFI-I48 was previously described as the MM2-thalamic form with widespread cortical pathology ( Hirose et al , 2006 ), and sFI-T00/06 showing partial SC was previously reported as a thalamic variant of sCJD with severe brain atrophy and plaque-like PrP deposition ( Yamashita et al , 2001 ). These results demonstrated that the combination of SC and OD was also commonly observed in the brains of patients with sFI, as previously reported ( Abu-Rumeileh et al , 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…sFI-I48 was previously described as the MM2-thalamic form with widespread cortical pathology ( Hirose et al , 2006 ), and sFI-T00/06 showing partial SC was previously reported as a thalamic variant of sCJD with severe brain atrophy and plaque-like PrP deposition ( Yamashita et al , 2001 ). These results demonstrated that the combination of SC and OD was also commonly observed in the brains of patients with sFI, as previously reported ( Abu-Rumeileh et al , 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, in a recent series of European sCJDMM2T, the two subjects with the longest disease duration (54 and 96 months) showed severe spongiform change in the striatum, which is usually relatively spared in this subtype, and one of them also demonstrated an atypical pattern of PrP staining characterized by sparse, small plaque‐like deposits in the cerebral cortex . Thus, in long‐lasting sCJDMM2T cases, spongiform change may not be limited to the cerebral cortex and PrP Sc aggregates may form small plaques in addition to the synaptic/fine granular pattern.…”
Section: Phenotypic Spectrum and Classification Of Disease Subtypesmentioning
confidence: 83%
“…The MM(V)1 subtype includes both MM1 and MV1 cases given that they are phenotypically indistinguishable, whereas the MM2 group comprises two subtypes with distinctive histopathological features and topographical distribution of lesions mainly affecting the cerebral cortex (MM2‐Cortical or MM2C) or the thalamus (MM2‐Thalamic or MM2T). The latter subtype is also known as the sporadic form of FI . It is also noteworthy that about 35% of sCJD cases show the co‐occurrence of PrP Sc types 1 and 2, an intriguing and still unexplained phenomenon that is more often observed in subjects carrying MM at codon 129 than in the other genotypes .…”
Section: Phenotypic Spectrum and Classification Of Disease Subtypesmentioning
confidence: 99%
“…* Ratio between diglycosylated and unglycosylated PrP Sc fragment; ° Lacks diglycosylated PrP Sc . Data summarized in the Table are taken from the following studies: disease frequency [32,60,69], disease duration [32,60,69,70], T50 [68], PK-resistance ED50, glycosylation and aggregation ratios [67], attack-rate and incubation time [71,72,73,74,75,76,77,78]. NA, not available; ND, not defined.…”
Section: Figurementioning
confidence: 99%